Factors Causing Fighting Behavior in Teenagers in Magelang - Musaini , Arizal; Safitri , Annisya Devi; Faizah , Rayinda (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This research was conducted with the aim of examining the factors that cause the emergence of adolescent behavior in Magelang. The research method used was descriptive qualitative, in which interviews were conducted with three teenagers who had the criteria of having been involved in fights. The results of the study state that the factors that cause fight behavior among adolescents in Magelang can be divided into two, namely internal factors and external factors. Internal factors consist of an identity crisis, weak self-control, and emotional instability. While external factors consist of the influence of the environment and conformity. The existence of this research is expected to provide an overview of the causes of the emergence of fighting behavior among adolescents in Magelang so that preventive measures can be developed against the emergence of fight behavior among adolescents.